Relevance of the Productive Course of Hair Beauty in Vocational High Schools to Industry Needs - Ambiyar, Ambiyar; Yulastri, Asmar; Yupelmi, Mimi; Paryono, Paryono (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
The problem primarily faced by vocational education institutions is a gap between skills taught at schools and skills required by the industries. This leads to the increasing unemployment rate of Vocational High School graduates. Thus relevant curriculum is required to satisfy the industry demands. This study aimed at analyzing the relevance of the productive course of hair beauty in Vocational High Schools to the job requirements in beauty salons in Padang. This study was qualitative descriptive. The data collection used interviews, observation and documentation. The data collection instruments consisted of observation sheets and interview guidelines. The data were analyzed using the stages of data reduction, presentation and conclusion. The results showed positive relevance of the productive course of hair beauty in Vocational High Schools to the job requirements in beauty salons in Padang. The skills learned in the schools were adequately relevant with the skills required by beauty salons, since from thirteen productive lessons taught in the schools, eleven of them were implemented and used in the workplaces.